Identification of a feedback loop involving β-glucosidase 2 and its product sphingosine sheds light on the molecular mechanisms in Gaucher disease - Schonauer, Sophie; Gerl, Mathias; Brügger, Britta (The journal of biological chemistry, 2017)
The lysosomal acid β-glucosidase GBA1 and the non-lysosomal β-glucosidase GBA2 degrade glucosylceramide (GlcCer) to glucose and ceramide in different cellular compartments. Loss of GBA2 activity and the resulting accumulation of GlcCer results in male infertility, whereas mutations in the GBA1 gene and loss of GBA1 activity cause the lipid-storage disorder Gaucher disease. However, the role of GBA2 in Gaucher disease pathology and its relationship to GBA1 is not well understood. Here, we report a GBA1-dependent down-regulation of GBA2 activity in patients with Gaucher disease. Using an experimental approach combining cell biology, biochemistry, and mass spectrometry, we show that sphingosine, the cytotoxic metabolite accumulating in Gaucher cells through the action of GBA2, directly binds to GBA2 and inhibits its activity. We propose a negative feedback loop, in which sphingosine inhibits GBA2 activity in Gaucher cells, preventing further sphingosine accumulation and, thereby, cytotoxicity. Our findings add a new chapter to the understanding of the complex molecular mechanism underlying Gaucher disease and the regulation of β-glucosidase activity in general.